Implementasi Activity-Centered Design Dalam Merancang User Interface E-Custom - Tedi Irawan; Lalu Mutawalli; Mohammad Taufan Asri Zaen (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2023)
Custom clothing has become a trend in the current era among young people. Custom clothing is interpreted as a request for goods or services made specifically to suit consumer personalization. This custom fashion trend has caused young people to become enthusiasts because they have a unique way of dressing and prefer to showcase their existence in appearance. Considering the large population of young people in Indonesia, the custom clothing business has significant market opportunities. Currently, many entrepreneurs have tried to start businesses in custom clothing. However, the challenge lies in aligning custom clothing with a platform for consulting on more personalized design preferences. Examining the youth market in Indonesia, which notably has a very large population, makes the custom clothing business have significant market opportunities. Many entrepreneurs have attempted to start businesses in custom clothing. However, the challenge is that custom clothing must be synchronized with a platform for consulting on more personalized design preferences. With the existence of media that can serve as a means between consumers and business actors, it will undoubtedly make the custom clothing business more adaptive, considering the habits of Generation Z, who prefer using digital media compared to visiting manufacturing locations directly. The problem faced by custom clothing business operators today, when viewed from both the consumer (customer) and producer (custom clothing business operator) sides, is that in order for issues from both the consumer and producer sides in the custom clothing ordering process to production to be well accommodated, a system is needed that can process the activities of both parties more easily with a user-friendly interface design. The User Interface starts with the Requirement phase to identify user needs. Next is the Design phase to create low-fidelity designs. In the Design Implementation phase, high-fidelity and interactive prototypes are created using Figma software. In the Design Evaluation phase, 20 assumptions about respondent acceptance of the e-custom user interface design were tested. The results showed that 15.8% strongly agreed, 21.1% were neutral, and 63.2% agreed. In the SUS (System Usability Scale) test, the user interface design scored 56. Based on this score, it can be hypothesized that the system has acceptability in the Marginal range, indicating a low category with a grade scale of F and an acceptance range at the Ok level, indicating that the design results are quite good based on user responses.